THU0324 CYTOMEGALOVIRUS REACTIVATION AND HIGH INITIAL SERUM CREATININE ARE SIGNIFICANT PROGNOSTIC FACTORS FOR SUBSEQUENT SEVERE INFECTIONS IN PATIENTS WITH ANCA-ASSOCIATED VASCULITIS. (2nd June 2020) - Waki, D.; Nishimura, K.; Yoshida, T.; Kadoba, K.; Tanaka, N.; Murabe, H.; Yokota, T.
Abstract : Background: There are several reports that cytomegalovirus (CMV) reactivation resulted in more co-infections affecting survival in rheumatic disease, and CMV reactivation can lead to infections in granulomatosis with polyangiitis patients by inducing CD4+CD28- T cell and depressing naïve T cell populations. 1-4 Despite this evidence, the prognostic value of CMV reactivation for severe infections in patients with connective tissue disease are still unknown. Objectives: The aim of this study was to examine prognostic factors for severe infection during the early phase of treatment, especially in CMV reactivation, in patients with antineutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis (AAV) who received initial high dose corticosteroid therapy (prednisolone > 0.8mg/kg/day). Methods: We analyzed the data of 88 consecutive hospitalized patients newly diagnosed with AAV at our hospital from January 2006 to March 2019 in this retrospective cohort study. There were 32 patients with CMV reactivation during remission induction therapy compared to 56 patients without CMV reactivation. CMV reactivation was defined by the detection of CMV pp65 antigen in blood samples, and CMV positive cells ≥ 5 per 3.0 × 10 5 polymorphonuclear neutrophils (PMNs). The variable for severe infections within 180 days with a p value < 0.1 in univariate analysis were selected for multivariate analysis using the Cox regression model. The positive predictive value (PPV) and positive likelihood ratio (PLR) of CMV reactivation for subsequent severe infections were also analyzed. Results: Patients with CMV reactivation, compared to those without, had a higher prevalence of MPO-ANCA, renal manifestation and renal impairment at diagnosis, received hemodialysis (HD), higher revised five factor score (FFS), older age, higher Birmingham Vasculitis Activity Score at diagnosis, and higher initial doses of corticosteroids (CS) at baseline. Revised FFS ≥ 2, renal involvement, high initial serum creatinine (≥ 1.5 mg/dl) at diagnosis, received HD, and CMV reactivation were associated with severe infections in the univariate analysis, although receiving cyclophosphamide or rituximab was not. Among these variables, CMV reactivation (Hazard ratio [HR] 3.50; 95% confidence interval [CI]: 1.22-10.10; p = 0.02) and high initial serum creatinine at diagnosis (HR 8.09; 95%CI: 2.00-32.73; p < 0.01) were independent risk factors for severe infections within 180 days. (Table 1 ) The PPV and PLR of CMV reactivation for subsequent severe infections were 35% and 1.91. When including higher initial serum creatinine, PPV and PLR for subsequent severe infections was 67% and 7.26. Conclusion: Our study shows that there should be focus on subsequent severe infections when CMV reactivation is detected during early phase of treatment, especially in renal-impaired patients with ANCA-associated vasculitis. References: [1]Gardiner BJ et al. Rheumatol Int. 2019;39:1229-40 [2]Hung M et al. J Microbiol Immunol Infect. 2019;52:114-21. [3]Hanaoka R et al. Mod Rheumatol. 2012;22:438-45. [4]Morgan MD et al. Arthritis Rheum. 2011;63:2127-37. Disclosure of Interests: Daisuke Waki Speakers bureau: Mitsubishi Tanabe Pharma, AbbVie Inc, eisai Co, . Ltd, ONO PHARMACEUTICAL CO., LTD, , Keisuke Nishimura Speakers bureau: Mitsubishi Tanabe Pharma Corporation. Pfizer Inc. Kyowa Kirin Co., Ltd. Chugai Pharmaceutical Co., Ltd. ONO PHARMACEUTICAL CO., LTD. Japan Blood Products Organization. Kissei Pharmaceutical Co., Ltd. Astellas Pharma Inc. AYUMI Pharmaceutical Corporation. Eisai Co., Ltd. DAIICHI SANKYO COMPANY. Norvartis AG. Bayer AG. Sanofi K.K., Tomohiro Yoshida: None declared, Keiichiro Kadoba: None declared, Nozomi Tanaka: None declared, Hiroyuki Murabe: None declared, Toshihiko Yokota: None declared